2002
DOI: 10.1207/s15327752jpa7903_06
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Chinese Psychological Well-Being With Western Developed Instruments

Abstract: We explored the possibility of applying 4 psychological scales developed and commonly used in the West to Chinese culture. The participants, 273 Chinese and 302 Americans, completed measures of self-esteem (Self-Esteem Scale; Rosenberg, 1965), depression (Center for Epidemiologic Studies-Depression Scale; Radloff, 1977), social support (Multidimensional Scale of Perceived Social Support; Zimet, Dahlem, Zimet, & Farley, 1988), and suicidal ideation (Scale for Suicide Ideation; Beck, Kovacs, & Weissman, 1979). A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
162
0
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 202 publications
(172 citation statements)
references
References 52 publications
7
162
0
3
Order By: Relevance
“…However, some support for treating the general concept of life satisfaction or subjective well-being as measured by the SWLS as relatively culture free comes from a study conducted by Zhang and Norvilitis (2002) who found that the concept of psychological well-being could be validly assessed in Chinese culture with Westerndeveloped instruments.…”
Section: Discussionmentioning
confidence: 99%
“…However, some support for treating the general concept of life satisfaction or subjective well-being as measured by the SWLS as relatively culture free comes from a study conducted by Zhang and Norvilitis (2002) who found that the concept of psychological well-being could be validly assessed in Chinese culture with Westerndeveloped instruments.…”
Section: Discussionmentioning
confidence: 99%
“…Higher scores indicate higher depression after reversing the four items. The CES-D scale demonstrate good psychometric properties in China among college students (Zhang and Norvilitis, 2002). Orme et al (1986) claimed that the scale demonstrates good factorial validity.…”
Section: Depression (Ces-d)mentioning
confidence: 99%
“…The scale has been used to assess social support among South Asians (Tonsing et al, 2012). In China, the scale is also reliable and valid for use (Zhang and Norvilitis, 2002).…”
Section: Social Support (Mspss)mentioning
confidence: 99%
“…Although the CES-D has been used primarily to assess depression in the United States, it has also been utilized in China (e.g., Cheng & Chan, 2005), Italy (e.g., De Gennaro et al, 2004), the Netherlands (e.g., Sonnenberg, 2003;Spijker, 2004), Japan (e.g., Nakata et al, 2007;Tanaka, 2006;Wada, 2007), Canada (e.g., Cameron et al, 2006Gatz, 2005), Australia (e.g., Alati et al, 2007;Almeida & Pfaff, 2005), and England (e.g., Sainz & Rey, 2007). Recently, Zhang and Norvilitis (2002) pointed out that this Western-developed instrument has been increasingly applied to the previously understudied populations in China and the reliability of the full CES-D has been demonstrated in a wide variety of samples with estimates of internal consistency ranging from .8 to .9 and test-retest reliabilities ranging from .4 to .7 (Devins et al, 1988). These investigators assessed the quality of the CES-D cross-culturally, finding that it was also reliable and valid based on their Chinese and Americans samples.…”
mentioning
confidence: 99%